Effect of positive emotions training on prevention of depression and anxiety: A study among senior high school students in Aceh, Indonesia - Fithria, Fithria; Aiyub, Aiyub; Nirwan, Nirwan; Agustina, Sri; Jannah, Syarifah Rauzatul (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: The high incidence of depression and anxiety, specifically among adolescents, needs special attention. These conditions, along with subclinical symptoms, are the leading causes of disability among this age group, which can impact their subsequent development process. Concerning these conditions, depression will also trigger suicidal thoughts among adolescents. Therefore, this study aimed to test the effectiveness of Positive Emotions Training (PoET) intervention in preventing depression and anxiety among adolescents in Aceh Besar, Indonesia.Study design and methods: This study involved two groups, namely the intervention and the control groups, and the resulting variable is a decrease in depression and anxiety scale. A total of 120 respondents from two Senior High Schools in Aceh Besar District were selected as a sample, including 68 respondents in the intervention group and 52 in the control group. Depression data was collected using Kovacs's Children's Depression Inventory (CDI), while anxiety data was measured using the Beck Anxiety Inventory (BAI).Results: The results of statistical tests using the Mann-Whitney Test showed that there was an effect of PoET intervention on levels of depression (p-value: 0.021) and anxiety (p-value: 0.001) in students.Conclusions: Based on these findings, it is recommended that health practitioners, specifically community health nurses and family health nurses, implement PoET intervention as a process to reduce levels of depression and anxiety among Senior High School students